2009
DOI: 10.1128/ec.00357-08
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Replacements in Toxoplasma gondii Strains Deficient for Nonhomologous End Joining

Abstract: A high frequency of nonhomologous recombination has hampered gene targeting approaches in the model apicomplexan parasite Toxoplasma gondii. To address whether the nonhomologous end-joining (NHEJ) DNA repair pathway could be disrupted in this obligate intracellular parasite, putative KU proteins were identified and a predicted KU80 gene was deleted. The efficiency of gene targeting via double-crossover homologous recombination at several genetic loci was found to be greater than 97% of the total transformants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
342
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(348 citation statements)
references
References 49 publications
4
342
1
1
Order By: Relevance
“…To access the impact of TgIF2α phosphorylation in Toxoplasma tachyzoites, we generated a mutant parasite line in which the Ser-71 residue of TgIF2α was substituted to alanine. The TgIF2α-S71A mutation was created by allelic replacement using homologous recombination in RHΔKu80 parasites (15,16). RHΔKu80 parasites were transfected with a "knock-in" construct that contained a point mutation encoding the S71A substitution along with a minigene encoding chloramphenicol resistance (Fig. Author contributions: B.R.J., R.C.W., and W.J.S.…”
Section: Resultsmentioning
confidence: 99%
“…To access the impact of TgIF2α phosphorylation in Toxoplasma tachyzoites, we generated a mutant parasite line in which the Ser-71 residue of TgIF2α was substituted to alanine. The TgIF2α-S71A mutation was created by allelic replacement using homologous recombination in RHΔKu80 parasites (15,16). RHΔKu80 parasites were transfected with a "knock-in" construct that contained a point mutation encoding the S71A substitution along with a minigene encoding chloramphenicol resistance (Fig. Author contributions: B.R.J., R.C.W., and W.J.S.…”
Section: Resultsmentioning
confidence: 99%
“…To date, bioinformatic analyses have failed to identify any Plasmodium homologs of NHEJ proteins (Table 1) (92). In contrast, another apicomplexan parasite, Toxoplasma gondii, carries a functional Ku-dependent NHEJ pathway (93), suggesting that despite relative evolutionary proximity to T. gondii, Plasmodium has lost its NHEJ machinery. In support of this hypothesis, a recent study showed the absence of any NHEJ products recovered from in vivo endonuclease-generated DSBs in Plasmodium (13).…”
Section: End Joiningmentioning
confidence: 99%
“…Gene knockout targeting plasmids were engineered to delete a short region of the gene's predicted 5= untranslated region (UTR) and the entire predicted coding region of the targeted genomic locus (www.ToxoDB.org, version 12.0). Targeting plasmids were first verified by restriction enzyme digest and were sequenced to verify 100% gene homology to the available type II ME49 genome sequence (17).…”
Section: Methodsmentioning
confidence: 99%